2020
DOI: 10.1371/journal.pntd.0008907
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of soil-transmitted helminth infections in Semarang, Central Java, Indonesia

Abstract: Soil-transmitted helminth (STH) infections are endemic in Indonesia. However, prevalence data for many parts of the country are incomplete. The aim of this study was to determine human STH prevalence and knowledge and practices relating to STH risk behaviour, to provide a current view of the status of STH infection in rural communities in Central Java. A cross-sectional survey of 16 villages was conducted in Semarang, Central Java in 2015. Demographic and household data together with information about knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 34 publications
2
15
0
1
Order By: Relevance
“…The present study also found that household heads in the lowest wealth percentile were 2.7 times more likely to be infected with STHs as compared to household heads in the highest wealth percentile. A similar result was reported from Kenya, Nigeria, Benin, Malaysia, and Indonesia, where individuals with low income were more affected by STHs than their counterparts [34,36,50,54,55]. Here we also found that household heads who possessed unimproved toilet facilities were two times more likely to be infected with STHs as compared to household heads who possessed improved toilet facilities.…”
Section: Plos Onesupporting
confidence: 90%
“…The present study also found that household heads in the lowest wealth percentile were 2.7 times more likely to be infected with STHs as compared to household heads in the highest wealth percentile. A similar result was reported from Kenya, Nigeria, Benin, Malaysia, and Indonesia, where individuals with low income were more affected by STHs than their counterparts [34,36,50,54,55]. Here we also found that household heads who possessed unimproved toilet facilities were two times more likely to be infected with STHs as compared to household heads who possessed improved toilet facilities.…”
Section: Plos Onesupporting
confidence: 90%
“…Wasilewska et al [ 47 ] found no association between BMIZ and Ascaris infection in children (OR = 0.98). Likewise, Kurscheid et al [ 32 ] found no association between BMI and Trichuris and/or hookworm and/or Ascaris infection. However, the results of both studies were not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…Soil is important in the life cycle of STH because it provides a warm, moist environment for eggs to incubate and become infectious [ 49 ]. Hookworm eggs require up to 14 days to become viable and infectious, A. lumbricoides eggs require between 8 and 37 days, and T. trichiura eggs require between 20 and 100 days [ 50 ]. Infectious eggs of Ascaris and Trichuris can survive for a few months, while hookworm larvae can survive for a few weeks.…”
Section: Resultsmentioning
confidence: 99%